RESPONS FISIOLOGI, PERTUMBUHAN, PRODUKSI DAN SERAPAN P BAWANG MERAH (Allium ascalonicum L.) TERHADAP PEMBERIAN TRICHOKOMPOS TANDAN KOSONG KELAPA SAWIT (TKKS) TERFORMULASI DAN PUPUK P DI LAHAN GAMBUT - ZALDI ARMAN; NELVIA NELVIA; ARMAINI ARMAINI (Jurnal Agroteknologi, 2016)
The study aims to determine the effect of formulated PEFB trichokompos and P fertilizers  on growth, physiology, production and P uptake of onion in peatlands. This research used experimental factorial randomized completely block design and three replications. Trichokompos PEFB formulated as the first factor is composed of four levels (0, 5, 10 and 15 ton ha-1) and P fertilizers as the second factor consists of four levels (0, 120, 180 and 240 kg ha-1 P₂O5). Parameters measured were chlorophyll content, photosynthesis rate, stomataH2Oconductivity , the concentration of CO2 in the cell, transpiration rate, plant height, number of tillers, number of tubers per hill, the diameter of the bulbs, fresh weight of tuber per hill, plant dry weight and P uptake. The results showed trichokompos PEFB formulated 15 ton ha-1 can increase the response of onion production as tuber diameter and fresh weight per hill and P uptake response respectively by 25.58%, 74.92% and 76.39%. While the physiological responses seen to decrease thestomatal H2O conductivity and transpiration rate of respectively 21.43% and 28.79% compared with no PEFB formulatedtrichokompos. Provision of fertilizer P 120 P2O5 ha-1 can improve physiological responses such as H2O on stomatal conductivity, increased growth responses such as plant height, such as the production response tuber diameter and fresh weight per hill and P uptake response respectively by 7.69%, 22.25%, 26.23%, 56.21% and 44.26% compared with no fertilizer P. combination trichokompos PEFB formulated 15 ton ha-1 with manure P 120 P2O5 ha-1 is the best treatment combination, with the highest production response namely 7.65 g (1.91 ton ha-1) fresh weight per hill and increased 214.81% compared with no treatment trichokompos PEFB formulated and fertilizer P.